2019
DOI: 10.3389/fgene.2019.01083
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Radial Spoke Head and Outer Dynein Arm Protein Defects and Ciliogenesis Abnormality in Nasal Polyps

Abstract: Background: Nasal polyp (NP) is a chronic upper airway inflammatory disease that is frequently triggered by defective host-defense. However, the mechanisms underlying the impaired barrier function such as cilia-mediated mucociliary clearance remain poorly understood. Objective: To assess ciliary ultrastructural and ciliogenesis marker expression and the phenotypes of ciliated cells in NP. Methods: NP biopsy samples were obtained from 97 NP patients and inferior turbinate from 32 healthy controls. Immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Abnormal expression of ciliary ultrastructural markers has been implicated in chronic lower airway inflammatory diseases that have previously been linked to genetic defects, such as DNAH5, DNALI1, GAS8 (a component of the nexin-dynein regulatory complex), RSPH4A, RSPH9 and RSPH1 . 24 , 25 According to literatures, secondary ciliary dyskinesia was found in patients with chronic rhinosinusitis, 7 , 8 , 26 , 27 bronchiectasis 28 and chronic obstructive pulmonary disease. 29 The abnormal ciliary ultrastructure consisted mainly of compound cilia, microtubular and dynein arm defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abnormal expression of ciliary ultrastructural markers has been implicated in chronic lower airway inflammatory diseases that have previously been linked to genetic defects, such as DNAH5, DNALI1, GAS8 (a component of the nexin-dynein regulatory complex), RSPH4A, RSPH9 and RSPH1 . 24 , 25 According to literatures, secondary ciliary dyskinesia was found in patients with chronic rhinosinusitis, 7 , 8 , 26 , 27 bronchiectasis 28 and chronic obstructive pulmonary disease. 29 The abnormal ciliary ultrastructure consisted mainly of compound cilia, microtubular and dynein arm defects.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Our published study has demonstrated the abnormal-regulation of ciliogenesis markers ( CP110 and FOXJ1 ) and overly dense and lengthened cilia, greater prevalence of absence of DNAH5, RSPH1, RSPH4A and RSPH9 expressions, and the significantly reduced ciliary beat frequency have also been observed in NPs in the aberrantly remodeled epithelium of NPs. 7 , 8 , 26 However, the characteristics of ciliary impairment in ACPs remain not fully explored. Therefore, according to the result of our sequencing analysis, we evaluated the expression of 9 common cilia-related genes and 2 ciliogenesis markers by qPCR analysis and IF staining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note also that abnormal expression patterns of RSPH1, RSPH4A, RSPH9, and DNAH5 were significantly more common in patients with nasal polyps, a chronic upper airway inflammatory disease that is frequently triggered by defective host-defense [58], even in the absence of classic PCD.…”
Section: Secondary Ciliopathymentioning
confidence: 94%